2021
DOI: 10.1038/s41598-020-80660-z
|View full text |Cite
|
Sign up to set email alerts
|

An experimental validation of partial discharge localization using electromagnetic time reversal

Abstract: The localization of partial discharge (PD) sources is of importance for the monitoring and maintenance of power transformers. Time difference of arrival (TDoA) based methods are widely adopted in the literature for the localization of PDs. Recently, time reversal (TR) was suggested as an efficient means to locate PD sources. As opposed to TDoA, which needs at least 4 sensors, TR is able to locate PD sources in power transformers with only one sensor. Moreover, it needs neither line-of-sight wave propagation fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The volume of the transformer tank, as shown in Fig. 1, is 1000 × 500 × 500 mm 3 . The thickness of the tank walls is 10 mm.…”
Section: Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The volume of the transformer tank, as shown in Fig. 1, is 1000 × 500 × 500 mm 3 . The thickness of the tank walls is 10 mm.…”
Section: Case Studiesmentioning
confidence: 99%
“…Any malfunction in a power transformer can result in power outages and reduced reliability of electrical power networks. Therefore, the early detection and localization of PDs is crucial in order to prevent potential hazards and minimize further damage 2,3 .…”
mentioning
confidence: 99%
“…More recently, time reversal (TR) in both the electromagnetic (EMTR) and the acoustic (ATR) regimes has been applied to locate PDs [15][16][17][18]. The TR technique can perform both 2D and 3D localization of multiple PD sources with only one sensor and does not require a line of sight.…”
Section: Introductionmentioning
confidence: 99%
“…In [14], it was shown that the reflections from the surfaces of a cavity can emulate an infinite number of sensors in the time-reversal method. The idea presented in [14] was later successfully applied to the localization of partial discharges (PDs) in power transformers [24][25][26]. The method was also found to be robust against variations in the polarization and length of the PDs and also against environmental noise.…”
Section: Introductionmentioning
confidence: 99%